Comprehensive Analysis of Pair Galaxy UGC 8335 Using Multiple Filters - Al-baqir, Haydar R.; Ahmed, Abdullah K. (Iraqi Journal of Science, 2024)
The two galaxies, UGC 8335 (East) E and (West) W, were investigated through the utilization of photometric and spectroscopic approaches, employing g, r, i, and z filters to gather the maximum amount of details feasible; the observed data ware obtained using the data releases (DR7 and DR17) provided by "The Sloan Digital Sky Survey (SDSS)." Subsequently, the data were fitted to ellipsoids through the utilization of "the Images Reduction & Analysis Facilities (IRAF)" through implementation of the STSDAS ELLIPS tool. Multiple characteristics of the two galaxies UGC 8335 E and W, have been scrutinized, including surface brightness, magnitudes, both vertical and horizontal changes, accumulated flux, central axis position angles, ellipticities, isophotal shape parameters (B4), and star-forming rates (SFRs), together with their astronomical characteristics. The UGC 8335 galaxy pair has been confirmed to be an interacting pair that exhibits significant indications of interaction and is undergoing a merging process. Furthermore, this combination is categorized as an intermediate galaxy pair and represents a physical set with refined star formation rates.